THE PROTECTION OF ROHINGYA REFUGEES IN INDONESIA ACCORDING TO THE INTERNATIONAL REFUGEE LAW - Medisita Nur Fauziah I (FH IH 16 UMY 062, 2016)
In recent decades the phenomenon of refugees increases year by year and becomes the attention of the international community. The states are supposed to be a safe place to live for its citizens, on the contrary their own government is the source of their torture. They, the Rohingyas is one of example of a state which do persecution and inhumane treatment toward their citizens. The Rohingyas is a minority ethnic which subjected a torture done by the junta military of Myanmar. The Rohingyas are stateless people, and they have no protection because the Government of Myanmar did not give the nationality status and did not acknowledge them as the citizens of Myanmar. That is the reason why the Rohingyas fled to another country to get a safe place to live. The problem arises when the Rohingyas came to Indonesia, and Indonesia has not ratified the 1951 Convention and its Protocol. The purpose of this research is to know and explain the protection of refugees according to the international refugee law also to understand the implementation of Indonesia to give the protection of the Rohingya refugees. This research uses normative legal research with statute and case approaches. By using a qualitative descriptive method, this study analyzes the Rohingya refugees according to the international refugee law such as 1951 Convention Relating to the Status of Refugees and 1967 Protocol. The result shows that the international protection for refugees is already protected by the 1951 Convention, and its protocol establishes fundamental rights to be acquired for refugees. Although Indonesia is non-state parties, Indonesia as a transit state did not force the Rohingyas to return to their habitual residence and facilitate the emergency needs of the Rohingyas. The Indonesian government should ratify and implement the 1951 Convention and its protocol to give status determination in this case is the Rohingyas. Keywords: The protection, refugees, Rohingya, persecution, the 1951 Convention